CHARACTERISTICS OF ECOLOGY OF BEE-EATERS (MEROPS APIASTER, M. SUPERCILIOSUS) IN DAGHESTAN AS A REGION OF INTENSIVE MIGRATIONS - E. V. Vilkov a (Юг России: экология, развитие, 2016)
Aim. Over the last twenty years the abundance of migratory populations of the European Bee-eater and Blue-cheeked Bee-eater on their migration routes in the region of the western coast of the Middle Caspian Sea, Daghestan has decreased. The goal of this research is to assess the current status of two studied taxa of bee-eaters and determine reasons inducing long-term fluctuations in their numbers in different parts of the range. Methods. The number dynamics of European and Blue-cheeked Bee-eaters was detected by long-term rows of observation data (1995-2015) in key points of their major flyways. The current status of European and Blue-cheeked  Bee-eaters in different parts of their range, including Daghestan, was identified by means of published data, personal observations and inquiries. Results. Their habitats, abundance trends, timing of migration and characteristics of migration behaviour in plain and mountainous areas of the republic were identified. It has been established that Daghestan is traversed by three independent and stable migration flows of bee-eaters, crossing this transit region along different migration channels. The studies showed that the aridization of climate has lead to the reduction of the bee-eater abundance on their major flyways. Main conclusions. Deterioration of habitats caused redistribution of the Daghestan population of the Blue-cheeked Bee-eater to the north of its range and changed migration routes of the European Bee-eater. A fact of fishing is described for both bee-eater species, which is for the Blue-cheeked  Bee-eater is an unprecedented case in the world science.